Pengukuran Kinerja Supply Chain Management pada Kantin Halal Soedirman dengan Pendekatan SCOR 12.0 dan Fuzzy Analytical Hierarchy Process (FAHP) - Arsil, Poppy; Hidayat, Hety Handayani; Wahyuni, Dewi (Institute of Research and Public Service Universitas Jenderal Soedirman, 2024)
The food service industries have a substantial contribution to the regional domestic income of Banyumas Regency. Residents of Banyumas Regency have an average monthly food expenditure of IDR491.837 per person in 2022. These indicate that the food and beverage industry possesses substantial economic potential. A food service enterprise is a popular type of food and beverage provider today. As a result, food service establishments must incorporate supply chain assurance into their operational procedures. Kantin Halal Soedirman is one of Purwokerto's food service restaurants. This study's objective is to assess the supply chain performance of Kantin Halal Soedirman so that the canteen may make the necessary adjustments to remain competitive in the food and beverage industry. Supply Chain Operations Reference (SCOR) 12.0, Fuzzy Analytical Hierarchy Process (FAHP), and Traffic Light System are the methodologies utilized in this investigation. The study's findings identified five primary business processes, namely plan, source, manufacture, dispatch, and enable. Furthermore, the analysis of all 30 metrics using the Traffic Light System revealed that 28 metrics showed green indicators, one metric showed yellow indicators, and one metric showed red indicators. In general, the assessment determined that the supply chain performance value at Kantin Halal Soedirman was 89.35%, falling within the satisfactory or very excellent category.